Variation in the straw traits of morphological fractions of faba bean (Vicia faba L.) and implications for selecting for food-feed varieties - Alkhtib, A.; Wamatu, Jane; Wegi, T.; Rischkowsky, Barbara A. (Elsevier, 2016)
Five varieties of faba beans, 4 improved and released variety and one local variety, were investigated for varietal variation in straw yield, nutritive value of straw morphological fractions and grain yield. Samples of the whole plant biomass were collected and separated into grain and straw. The straw was further divided into leaves, stems and pods. Straw samples were analyzed for their chemical composition, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME). The potential utility index (PUI) was employed to rank the varieties. The results demonstrated significant varietal variation in grain yield, straw yield and proportions of botanical fractions of straw. The improved varieties were superior to the local variety in grain yield, straw yield and PUI. The local variety had the highest proportion of stem and lowest proportion of leaf and pods. Significant varietal variations (P < 0.001) were detected in dry matter (DM), organic matter (OM), ash, IVOMD, ME but not in crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) of whole straw. The leaves showed the highest IVOMD and content of crude protein, while pods were highest in ME. Canonical correlation analysis showed significant (P < 0.001) correlations between the nutritive value of whole straw and nutritive value and proportions of its botanical fractions. Grain and straw yields were positively, strongly and significantly (P < 0.001) correlated. Weak correlations were detected between grain yield and straw quality traits. Ranking the varieties differed when grain yield, straw quality scores and PUI were considered. However the weak correlation existed between grain yield and straw quality, including straw quality index or PUI to select food-feed varieties of faba bean is still necessary. These findings indicate the possibility of selecting faba bean varieties which combine superior grain and straw traits.